2012
DOI: 10.1159/000336995
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Matrix Metalloproteinases and Their Tissue Inhibitors in Inflammatory Bowel Diseases

Abstract: Background: It has been suggested that matrix metalloproteinases (MMPs) may play a role in the pathogenesis of inflammatory bowel diseases (IBD). However, the impact of serum MMPs and their inhibitors [tissue inhibitors of metalloproteinases (TIMPs)] have scarcely been investigated in the same experimental setting in ulcerative colitis (UC) and Crohn’s disease (CD) as well as their correlation with IBD activity. Methods: MMP-2, MMP-7, MMP-9, TIMP-1 and TIMP-2 serum antigen levels were determined in 23 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 122 publications
16
49
0
Order By: Relevance
“…We confirm the previous observations made by Lakatos et al 4 in their study which demonstrated that serum antigen concentrations TIMP-1 were significantly increased in patients with UC and CD compared to controls. These data are in agreement with our study in which TIMP-1 antigen levels were highest in the IBD group (p<0.006).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We confirm the previous observations made by Lakatos et al 4 in their study which demonstrated that serum antigen concentrations TIMP-1 were significantly increased in patients with UC and CD compared to controls. These data are in agreement with our study in which TIMP-1 antigen levels were highest in the IBD group (p<0.006).…”
Section: Discussionsupporting
confidence: 93%
“…These proteins have been shown to be associated with disease activity as well as extraintestinal finding development. 4 The function of MMPs, a family of Zn 2+ -dependent endopeptidases, in the degradation of extracellular matrix components during tumor invasion and metastasis as well as their role in the processes of tissue destruction and remodeling during inflammation have been proposed. [5][6][7] The natural inhibitors of MMPs are called tissue inhibitors of metalloproteinases (TIMPs).…”
mentioning
confidence: 99%
“…Population-based studies have found that approximately 20% of patients developed fibrotic stricture within 20 years of a CD diagnosis; > 30% develop this complication within 10 years of diagnosis at tertiary referral centers. About 50% CD patients will develop penetrating or fibrotic strictures, and 70% of them will need surgery eventually [6][7][8]. Surgery is the only choice for symptoms/ complex stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…The tissue damage in IBD is mediated by an overactive mucosal immune response arising from a complex interplay of genetic, environmental and immunological factors. In the pathophysiological process of IBD, a variety of inflammatory mediators such as proteolytic enzymes, cytokines, reactive oxidative species, and growth factors are implicated in the complex tissue injury processes [1,2,3,4]. The link between IBD and colorectal cancer (CRC) has been described nearly a century ago [5].…”
Section: Introductionmentioning
confidence: 99%